Propagação de rumor em uma população cética em N - Higashizawa, Lissa Kido (Universidade Federal de São Carlos, 2023)
We consider two models for information propagation in N. In both models, the individuals (one per site of N) have random, independent, and equally distributed radius. At the beginning only the individual at 0 has the information. In the first model, the “firework model”, each informed individual will inform the individuals to its right that are within its radius, in the “reverse firework model”, each individual will get the information from the informed individuals on its left that are within its radius. The necessary and sufficient conditions are already known in the literature about the distribution of radius to have survival (positive probability of having infinitely many informed individuals) in each model. In this dissertation, we will obtain results for the extension of these models when individuals believe the information (get informed) only if they receive it (or take it) from at least 2 informed individuals.
Rumor propagations in a skeptical population on N
Keywords: Cadeia semi-Markov; Probabilidade; Processo de renovação; Processo firework; Processo firework cético; Semi-Markov chain; Probability; Renewal process; Firework process; Skeptical firework process; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::PROBABILIDADE